Peran Regulasi Emosi sebagai Moderator dalam Hubungan antara Stres Akademik dan Cyberslacking: Tantangan Sosial di Era Digital - Ida Bagus Gde Agung Yoga Pramana; Putu Riana Artyanti Putri; Ratna Devy Winayanti; Ni Wayan Yuli Anggreni; Ni Nyoman Imas Pradnyanita Wistarini; Putu Ayu Onik Pratidina (Universitas Hamzanwadi, 2025)
Academic stress, stemming from elevated academic expectations, frequently incites maladaptive behaviors such as cyberslacking, defined as engaging in non-academic internet activities during study periods. Emotion regulation, as a skill for a person to manage emotions in an adaptive way, and the presence of social support factors are thought to moderate this link. This study seeks to examine the function of emotion regulation as a moderating factor in the correlation between academic stress and cyberslacking among university students. This research utilizes a quantitative methodology with a correlational framework, encompassing 134 undergraduate students in Denpasar. Data were gathered via online questionnaires and processed with Moderated Regression Analysis (MRA) using SPSS version 25. The findings demonstrate that academic stress exerts a positive and significant influence on cyberslacking (β = 1.300; p < 0.05). Emotion regulation moderates the association between academic stress and cyberslacking (β = 0.019; p < 0.05), indicating that students with high emotion control are more likely to cope with stress without resorting to cyberslacking. The findings indicate that emotion control may act as a protective factor in mitigating the adverse effects of academic stress on cyberslacking.